Digital Distraction: The Negative Impact of Technology on Attention and Cognitive Focus in Young Minds - Alannah Grace Kuhn (Lembaga Pengembangan Kinerja Dosen, 2026)
Attention span and cognitive focus in young minds these days are increasingly structured by the growing influence of digital distractions. Drawing from the ideas of Foucault and Nietzsche, this paper examines how technology molds behavior and, at the same time, is used as a tool of control through power relations. This digitally fosters a form of nihilism, the sense life has no purpose. By using a mixed-methods approach, this research combines the surveying and in-depth interviewing of students and instructors about how technology influences attention, learning, and academic performance. Results indicate that while technology brings many benefits, it also provides significant challenges-most notably via social media and smartphone distractions. These distractions reduce attention spans, decrease deep learning, and contribute to cognitive overload. This study therefore calls for the integration of technology into education in a balanced way, highlighting digital literacy, mindful use, and distraction-reduction strategies. In the process, self-awareness, self-regulation, and responsible use will allow people to use its benefits rather than fall into disengagement and cynicism. Technology should serve as a tool for learning and growth-not a barrier to focus and intellectual development.